Cardiac Rehabilitation Availability and Density around the Globe. (August 2019) - Turk-Adawi, Karam; Supervia, Marta; Lopez-Jimenez, Francisco; Pesah, Ella; Ding, Rongjing; Britto, Raquel R.; Bjarnason-Wehrens, Birna; Derman, Wayne; Abreu, Ana; Babu, Abraham S.; Santos, Claudia Anchique; Jong, Seng Khiong; et al.
Abstract: Background: Despite the epidemic of cardiovascular disease and the benefits of cardiac rehabilitation (CR), availability is known to be insufficient, although this is not quantified. This study ascertained CR availability, volumes and its drivers, and density. Methods: A survey was administered to CR programs globally. Cardiac associations and local champions facilitated program identification. Factors associated with volumes were assessed using generalized linear mixed models, and compared by World Health Organization region. Density (i.e. annual ischemic heart disease [IHD] incidence estimate from Global Burden of Disease study divided by national CR capacity) was computed. Findings: CR was available in 111/203 (54.7%) countries; data were collected in 93 (83.8% country response; N = 1082 surveys, 32.1% program response rate). Availability by region ranged from 80.7% of countries in Europe, to 17.0% in Africa (p < .001). There were 5753 programs globally that could serve 1, 655, 083 patients/year, despite an estimated 20, 279, 651 incident IHD cases globally/year. Volume was significantly greater where patients were systematically referred (odds ratio [OR] = 1.36, 95% confidence interval [CI] = 1.35–1.38) and programs offered alternative models (OR = 1.05, 95%CI = 1.04–1.06), and significantly lower with private (OR = .92, 95%CI = .91–.93) or public (OR = .83, 95%CI = .82–84) funding compared to hybrid sources. Median capacity (i.e., number of patients a program could serve annually) was 246/program (Q25-Q75 = 150–390). The absolute density was one CR spot per 11 IHD cases in countries with CR, and 12 globally. Interpretation: CR is available in only half of countries globally. Where offered, capacity is grossly insufficient, such that most patients will not derive the benefits associated with participation.